2019
DOI: 10.7555/jbr.32.20160030
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of caspase-8 -652 6N del polymorphism and digestive tract cancer risk

Abstract: Caspase-8 (CASP8) is one key regulator of apoptosis of T lymphocytes and is encoded by the CASP8 gene. It has been reported that the six-nucleotide deletion polymorphism (-652 6N del) of the CASP8 gene had effect on some cancer risk. Few studies explored the association between CASP8 gene polymorphism and digestive tract cancer risk. To evaluate the association between the CASP8 -652 6N del polymorphism and the risk of digestive tract cancer, we conducted this meta-analysis. We found that CASP8-652 6N del poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…These highlight findings are also consistent with a previous report investigating the contribution of Cas- have conducted a meta-analysis to investigate the association between the Cas-8 rs3834129 polymorphisms and the risk for digestive tract cancers (39). They found an evident association between Cas-8 rs3834129 polymorphisms and reduced digestive cancer risk, especially for Asians (22). Future studies investigating the association of Cas-8 rs3834129 polymorphism and the risk of NPC in larger and different populations are urgently required to confirm our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These highlight findings are also consistent with a previous report investigating the contribution of Cas- have conducted a meta-analysis to investigate the association between the Cas-8 rs3834129 polymorphisms and the risk for digestive tract cancers (39). They found an evident association between Cas-8 rs3834129 polymorphisms and reduced digestive cancer risk, especially for Asians (22). Future studies investigating the association of Cas-8 rs3834129 polymorphism and the risk of NPC in larger and different populations are urgently required to confirm our findings.…”
Section: Discussionsupporting
confidence: 91%
“…There are at least 353 SNPs in Cas-8 reported in the NCBI dbSNP database. Cas-8 SNPs, such as D302H (rs1045485), IVS12-19G/A (rs3769818), and the promoter rs3834129 that will be the focus of the current study, have been reported to be potential genomic markers for the prediction of risk for several types of cancer such as neuroblastoma (17), breast cancer (18)(19)(20), lung cancer (21), digestive tract cancer (22,23), prostate cancer (24), and bladder cancer (25). However, the role of Cas-8 polymorphisms in NPC is not known.…”
mentioning
confidence: 99%
“…This leads to mitochondrial permeabilization executed by BCL2-associated X protein and BCL2 antagonist/killer protein (5). As for the association between CASPs and cancer, Du et al (13) explored the effects of a six-nucleotide deletion polymorphism of the CASP8 gene in the digestive tract on the risk of cancer development; all genetic models exhibited protection against the development of GC. The antitumor effects of CASPs were also investigated by Kanehara et al (14), in which the degree of CASP8 activation could indicate the anticancer potential of this CASP.…”
Section: Discussionmentioning
confidence: 99%
“…Among the polymorphic sites of CASP8, rs3834129 (-652, 6N ins/del) polymorphism, a six-nucleotide insertion (I)/deletion (D) variant, has been functionally identified to lead to down-regulation of the mRNA of CASP8 (18). Caspase-8 single nucleotide polymorphisms are reported to be genomic markers for the prediction of the personal risk for several types of cancers such as that of the digestive tract (19,20), breast (21)(22)(23), prostate (24), lung (25) and bladder (26), and neuroblastoma (27). Little is known about the role of CASP8 polymorphisms in oral cancer.…”
mentioning
confidence: 99%